Utility of a palatal speech appliance combined with the five-point eight-line segment technique in total tongue reconstruction. Issue 8 (August 2022) - Han, S.-W.; Hong, X.-W.; Li, H.; Han, W.
Abstract: The aim of this study was to explore a new total tongue reconstruction strategy based on the five-point eight-line segment (FIPELS) technique and a palatal speech appliance, and to evaluate the functional and aesthetic outcomes. Twenty patients with tongue squamous cell carcinoma were included in this study. All patients underwent total tongue resection followed by tongue reconstruction with an anterolateral thigh flap. The patients were divided randomly into two groups according to the reconstruction strategy: FIPELS group (10 patients) and traditional flap design group (10 patients). All 10 patients in the FIPELS group received a palatal speech appliance 1 month after the surgery. A Likert scale was used to assess swallowing function, speech articulation, and the aesthetic outcome of the reconstructed tongue in the traditional and FIPELS (with and without the palatal speech appliance) groups. Compared with the traditional group, swallowing function (1 month, P = 0.016; 3 months, P = 0.021) and the aesthetic outcome (1 month, P = 0.016; 3 months, P = 0.020) were significantly better in the FIPELS group (without the palatal speech appliance); however, there was no significant difference in speech articulation (1 month, P = 0.549; 3 months, P = 0.513). Within the FIPELS group, significantly better speech articulation was obtained with the palatal speech appliance than without it (1 month, P = 0.031; 3 months, P = 0.015).